Implementasi Kebijakan Hukum Agraria Terhadap Pembagian Hak Tanah Garapan di Desa Sampali Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Dahlia Natalia Lumban Gaol; Fani Nolpiana Nadapdap; Johana Andriani Nainggolan; Muhammad Hafis Faisal; Rahma Dhani Fitria Sinaga; Wulan Ayu Trisna; Yana Sebha Pasaribu; Ramsul Nababan (Jurnal Hukum dan Sosial Politik, 2024)
This research discusses the implementation of agrarian law policies regarding the distribution of rights to cultivated land in Sampali Village, Percut Sei Tuan District, Deli Serdang Regency. This study was conducted with the aim of analyzing the impact of policies, the level of community participation, and the factors that influence the implementation of these policies. The research method is descriptive qualitative which involves literature study, field study and interviews. The research results show that the implementation of agrarian law policies has had positive impacts such as changes in land ownership status, but also has negative impacts such as conflict and legal uncertainty. The level of community participation is proven to have a crucial role in the success of policy implementation. Factors such as unequal distribution of land, legal uncertainty, and lack of community involvement are obstacles to policy implementation in Sampali Village. It is recommended to revise agrarian law policies by considering input from the community and increasing their participation in the decision-making process. Strengthening institutions at the local level, participatory conflict resolution, and developing educational programs were also identified as important steps to improve sustainability and fairness in policy implementation. It is hoped that this research can contribute to a better understanding of the dynamics of agrarian law policy implementation at the local level and become a basis for improving policies that are more effective and inclusive.